Chapter The Potential of the Photoautotroph Synechocystis for Metal Bioremediation - Naveena, Balakrishnan; Armshaw, Patricia; Tony Pembroke, J. (InTechOpen, 2015)
Pollution & threats to the environment
English
Keywords: Pollution & threats to the environment; Earth sciences, geography, environment, planning